The role of extended scope physiotherapists in managing patients with inflammatory arthropathies: a systematic review - Stanhope J (Dove Medical Press, 2012)
Jessica Stanhope,1 Kate Beaton,1 Karen Grimmer-Somers,1 Joanne Morris21International Centre for Allied Health Evidence (iCAHE), University of South Australia, Adelaide, South Australia; 2ACT Government Health Directorate, Canberra, Australian Capital Territory, AustraliaObjectives: To review the literature to identify whether, and how, physiotherapists working in extended scope of practice (ESP) engage with patients with inflammatory arthropathies. Measures of effectiveness of ESP were particularly sought.Methods: A comprehensive library database search was conducted to identify English language studies published in full text in peer-reviewed journals during the years 2002–2012. Studies were allocated into the National Health and Medical Research Council hierarchy of evidence, but were not critically appraised. Data was extracted on conditions treated, ESP roles and responsibilities, and effectiveness. Data was analyzed and reported descriptively.Results: We identified 123 studies, and included four. All were low hierarchy (highest being one level III_2 study). Commonly reported conditions were rheumatoid arthritis and ankylosing spondylitis. Information was provided on activities of role extension, such as triaging patients, monitoring and recommending changes to medications, referring to other health and medical professionals, and ordering and interpreting imaging. There was blurring between ESP and non-ESP roles. No study reported measures of effectiveness.Conclusion: There are descriptors of ESP physiotherapy activities, but no evidence of effectiveness of ESP physiotherapy in managing patients with inflammatory arthropathies.Keywords: ESP, extended scope, rheumatoid arthritis, ankylosing spondylitis, inflammatory arthropathy, physiotherapy